Avaliação da atividade biológica de triazenos inéditos complexados com Au(I) - Kempfer, Cláudia Barbisan (2013)
The Triazenes are compounds with proven antibacterial and cytotoxic activity. Variations in the chemical structure such as complexation with metals like gold (I) can confer different biological activities. The antineoplastic temozolomide and dacarbazine are examples of commercially available triazenes used in the treatment of solid tumors and acute leukemias. In this study, the following compounds were synthesized triazenes complexed with novel gold (I): 1) [1,3-Bis (2-fluorophenyl) triazenido] (triphenylphosphine) gold (I); 2) [1,3-Bis (2- chlorophenyl) triazenido] (triphenylphosphine) gold (I) 3) [1,3-Bis (2-bromophenyl) triazenido] (triphenylphosphine) gold (I), 4) [1,3-Bis (2-iodophenyl) triazenido] (triphenylphosphine ) gold (I). Cytotoxicity of these compounds was evaluated by the MTT colorimetric assay of cell culture effecting bone marrow of patients with different types of leukemia, in addition to controlling patient without the disease. For the analysis of the antimicrobial activity was utilized quantitative methodology of microdilution with the determination of minimum inhibitory concentration (MIC). To determine the activity of nuclease cleavage assays were performed in double-stranded plasmid DNA using the method of electrophoresis in agarose gel. The results showed a considerable activity against different types of leukemia (acute myeloid leukemia, chronic myeloid leukemia, acute lymphoblastic leukemia, chronic lymphocytic leukemia) with a small IC50 value of 0.0057 μmol mL-1 for compound 4 in cells of acute myeloid leukemia, all the active compounds in different types of leukemia but not so selective. The antibacterial activity was higher against gram-positive bacteria mainly in different strains of Staphylococcus aureus (MIC value of equal to 16 ug/ml). Any of the four compounds analyzed in this study was able to cleave the plasmid DNA. Thus, all tested triazenes have biological potential, or may be the subject of further studies as alternatives to anticancer and antimicrobial drugs existent.